Weakly $(1,2)^*$-Fuzzy Generalized-closed Sets - P.Saravanaperumal; S. Murugesan (International Journal of Mathematics And its Applications, 2016)
In this paper, a new class of closed set called weakly (1,2)*-fg-closed set and new class of maps namely Weakly (1,2)*-fg continuous map, Weakly (1,2)*-fg open and Weakly (1,2)*-fg closed maps are introduced and their properties are studied.